2018
DOI: 10.1002/jum.14851
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Real‐Time Elastography in the Differential Diagnosis of Salivary Gland Tumors

Abstract: Objectives-The aim of the study was to scrutinize the value of qualitative elastography in the diagnosis of salivary gland masses.Methods-Sixty patients were enrolled in this prospective study. Patients aged between 1 and 91 years (mean age, 48.8 ± 20.48) with a salivary gland mass were studied with real-time elastography. All patients were examined by 1 examiner, blinded to all relevant data. On elastography, masses were scored into 4 types according to their stiffness compared to normal tissue. Scores of 3 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…Larger prospective studies are needed to determine the value of this investigation. USE recorded a pooled Se of 67%, a Sp of 64% and a diagnosis odds ratio of 8.00 in a meta-analysis [34] that evaluated the value of this investigation in the differential diagnosis of parotid tumors [9,26,34,35,36].…”
Section: Ultrasound Elastographymentioning
confidence: 99%
“…Larger prospective studies are needed to determine the value of this investigation. USE recorded a pooled Se of 67%, a Sp of 64% and a diagnosis odds ratio of 8.00 in a meta-analysis [34] that evaluated the value of this investigation in the differential diagnosis of parotid tumors [9,26,34,35,36].…”
Section: Ultrasound Elastographymentioning
confidence: 99%
“…The diagnostic accuracy of conventional SE in this study tended to be lower than that reported previously (Cortcu et al 2018;Karaman et al 2019). The eSie Touch imaging used in this study as conventional SE was selected on the basis of numerical parameters (strain quality indicator >50).…”
Section: Discussionmentioning
confidence: 69%
“…However, previous studies, with diagnostic accuracies >80%, may have had image selection bias. It is also possible that the wide range of diagnostic accuracy of conventional SE published in previous reports (55.4%À94.0%) might have been caused by image selection bias and the experience level and skill of examiners (Bhatia et al 2010;Dumitriu et al 2011;Celebi and Mahmutoglu 2013;Li et al 2016;Cortcu et al 2018;Karaman et al 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-sectional area (CSA) of the median nerve within the carpal tunnel inlet and outlet is the parameter of interest measured to reflect the severity of CTS ( 7 ) . As an extension to conventional US, sonoelastography (SE) has been introduced to map the local distribution of elasticity in biological tissues ( 8 , 9 ) .…”
Section: Introductionmentioning
confidence: 99%